Understanding nation-state attacks. Issue 10 (October 2017) - Lundbohm, Eric
Abstract : For the past three years the world has been going through an unprecedented increase in malicious cyber activity. Ransomware has mined a source of money that didn't exist just a few years ago. The emergence of nation states using cyber-attacks and breaches to further their agendas has caused an explosion of new threats against which every network must now have defences that work. The world has been going through an unprecedented increase in malicious cyber activity. The emergence of nation states using cyber-attacks and breaches to further their agendas has caused an explosion of new threats. Eric Lundbohm of Veracity Industrial Networks examines the emergence of cyber-warfare, the threats it poses and what we do about it. He concludes that we live in a world where battles are and will increasingly be fought in cyberspace rather than on the ground and in the air. While this is a cleaner style of war, it is no less of a menace.